Optimalisasi Investasi Pendidikan untuk Pertumbuhan Ekonomi Berkelanjutan - Zakiah Nurul Fitri; Nanda Nur Hafizhah; Hasnah Hasnah; Hasna mustika Zahra; Ani Rahmaindah; Rafael Frizy Rajagukguk; Adif Nur Amanulloh; Fauzi Wiramadan; Ere Mardella Arbiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Education has long been recognized as a primary determinant of economic progress and human development , yet in the context of a global economy characterized by rapid technological change and the sustainability imperative, the focus shifts from the mere quantity of investment to its effectiveness in fostering sustainable economic growth. Current education systems face significant challenges, including a persistent global